Pembaruan Islam Bidang Keluarga dan Relevansinya dengan Peraturan Poligami di Indonesia - Karimullah, Suud Sarim (El-Izdiwaj: Indonesian Journal of Civil and Islamic Family Law, 2021)
If the arrival of Islam equitably regulates the polygamy procedure, this is the same as the presence of marriage regulations in Indonesia. Law of the Republic of Indonesia Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage is a marriage regulation in Indonesia, one of which aims to provide legal certainty for polygamy in Indonesia. This article examines the Islamic reform in the family sector, especially on the issue of polygamy before Islam, after Islam came, and the rules of polygamy in Indonesia and how they are relevant between Islamic reform in the family sector and the rules of polygamy in Indonesia. Then, the library research is a data collection method used in writing this article with an analytical descriptive nature. Meanwhile, making it as additional knowledge and further reference in studying polygamy and its legal regulations in Indonesia is the goal expected in the preparation of this article. This article concludes that polygamy in Islam and marriage regulations in Indonesia are strictly regulated so that there is no mistreatment of women and try to provide protection and cover discrimination perpetrated by men against women in family life.